Rugby injury surveillance and prevention programmes: are they effective?. (21st April 2015) - Freitag, Andreas; Kirkwood, Graham; Pollock, Allyson M
Abstract : Despite the high rates of injury in rugby, the UK government plans to focus on increasing participation in the sport in schools. Andreas Freitag, Graham Kirkwood, and Allyson Pollock discuss whether surveillance and prevention programmes from around the world have reduced rugby injuries